Touring Shakespeare: The Stratford Festival, Cultural Funding, and Cultural Diplomacy - Dougherty, Sarah (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2018)
This article examines three key tours of the Stratford Festival from 1967 to 1986. In 1967, the Festival undertook its first and only cross-Canada tour in celebration of the Centennial. In 1973, the Festival staged its most direct production of cultural diplomacy with a Department of External Affairs sponsored tour of Europe. The Festival also went on a substantial tour of the United States in the winter of 1985/1986 with support from External Affairs. During these moments when the company left Stratford to perform elsewhere, the theatre brought with it a performance not only of Shakespeare but also of purported Canadian culture, and was motivated by not only by a cultural agenda but also a commercial one. Drawing on archival records of the Festival’s tours and attempts to gain state funding, this article charts the Festival’s turn away from domestic national touring to international touring and the calculations, done by both the theatre and the state, of the value involved in prioritizing touring outside of Canada over touring the nation. Ultimately, touring Canada was expensive, and was not seen as giving the same return on investment in terms of nationalist prestige, cultural diplomacy, and the attraction of tourists. I argue that through a claim to Canadian national culture, the Stratford Festival attempted to secure state support, with commercial interests for the Festival and town of Stratford at stake.